Analysis of mixing in stirred vessels using CFD: waste cooking oil transesterification - Adeyemi, Nabeel A.; Mohiuddin, A. K. M.; Abd Aziz, Abd Rashid; F., Firmansyah; Anbese, Yohannes Tamirat (2011)
A stirred laboratory reactor for transesterification of waste cooking oil (WCO) has been modeled using ANSYS 12 workbench. The reactor is used to evaluate the kinetics of reaction for oil transesterification. The internal configuration of the reactor is considered important to model the reactive flow assuming a uniform velocity profile in the tank. The FAME yield was correlated using different flow model to simulate scenarios for the given system and the solutions obtained using ANSYS Fluent agreed with validation calculations. Finally, a transient study demonstrated the effect of different impeller types used in the laboratory on Fatty Acid methyl Esters (FAME) yield in the reactor. This model can be used and built upon to evaluate other conditions of the reactions.